Pemberdayaan Masyarakat Melalui Edukasi Dan Literasi Gerakan Gaya Hidup Halal - Dwi Vita Lestari Soehardi; Andru Lumintang; Winanda Vathul Jannah4; Adelia Khairun Nida (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The halal factor is an important thing for Muslims in meeting their needs and desires. Halal means allowed in Islam. It should be supported in its implementation in habits or lifestyles. But in reality, many halal concepts are focused on food and drink alone. In fact, not only that, but also seen from the factors of safety, cleanliness, quality and all the goodness of what is consumed. In the halal industry, it is mentioned that in addition to food and beverages, it consists of Islamic Financial Institutions, Halal Tourism, Halal Fashion, Halal Pharmaceuticals and also Halal Cosmetics. Halal Lifestyle education is needed as one of the solutions to problems due to the low awareness and understanding of the millennial generation and generation z about the concept of halal and halal lifestyle. This paper is intended to share the urgency of halal literacy to increase knowledge and increase awareness in the application and intensify the halal lifestyle movement.